Analisis Pengambilan Keputusan Keuangan dan Pengaruhnya Terhadap Pertumbuhan UMKM Cibay di Kabupaten Karawang - Widianingsih, Astari; Haryadi, Raka; Anggeriani, Shefi; Capni, Angelina Airawadhi; Suherman, Ujang (PENG: Jurnal Ekonomi dan Manajemen, 2025)
UMKM Has an Important Role in the Economy. Where UMKM performance is very necessary so that UMKM goals are met in the HR Competence owned by UMKM determines the course of UMKM performance, the next stage is in the form of a Simple Financial Management Model. The current macro environmental conditions are not so conducive to the implementation of UMKM activities. UMKM also carries out and forms business networks to expand UMKM partnerships, and facilitates cooperation with other parties so that UMKM performance can run well. Efforts to improve performance are very important, especially those related to HR competency, macro environmental conditions and business networks carried out by UMKM. The purpose of this study is to determine the effect of HR Competence and how to process finances, Macro Environment and Business Networks on the Performance of UMKM Cibay (Aci Ngambay) in Karawang. So that this study is useful for adding references to the condition of UMKM performance related to HR compensation and financial management, macro environment and business networks. From the results of this study, two methods were used, namely direct observation and interviews at one of the food businesses, namely Cibay ((Aci Ngambay) precisely in front of the Karawang Square, it can be seen that currently in 2024 this Cibay business already has 4 HR staff. The discussion of this study is to analyze and describe the empowerment of Micro, Small and Medium Enterprises (MSMEs) HR from the start of the business, business success, business failure to surviving until now. Conclusions on financial management that are commonly used and provide information related to how to use working capital management for Mrs. Fitri's business so that the financial management used can help increase sales of food made by Mr. Jaky as an MSME actor.